2001
DOI: 10.1183/09031936.01.00229901
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine modulators as novel therapies for airway disease

Abstract: Cytokine modulators as novel therapies for airway disease. P.J. Barnes. #ERS Journals Ltd 2001. ABSTRACT: Cytokines play a critical role in orchestrating and perpetuating inflammation in asthma and chronic obstructive pulmonary disease (COPD), and several specific cytokine and chemokine inhibitors are now in development for the future therapy of these diseases.Anti-interleukin (IL)-5 is very effective at reducing peripheral blood and airway eosinophil numbers, but does not appear to be effective against sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
0
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 102 publications
3
47
0
9
Order By: Relevance
“…Neutrophils have also been shown to be a key effector cell of matrix breakdown in an animal model (8,9). Due to the fact that neutrophil recruitment in humans requires activation of the CXCR1 or CXCR2 receptors by CXC chemokines, these interactions have been explored as potential therapeutic targets (2,12). In mouse models of inflammation, neutrophil recruitment can be blocked by treatment with antibodies to MIP-2 and KC, CXCR2 antibodies (mice lack CXCR1), and CXCR2 antagonist peptides derived from CXCR2 ligands (14,17,21,37).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils have also been shown to be a key effector cell of matrix breakdown in an animal model (8,9). Due to the fact that neutrophil recruitment in humans requires activation of the CXCR1 or CXCR2 receptors by CXC chemokines, these interactions have been explored as potential therapeutic targets (2,12). In mouse models of inflammation, neutrophil recruitment can be blocked by treatment with antibodies to MIP-2 and KC, CXCR2 antibodies (mice lack CXCR1), and CXCR2 antagonist peptides derived from CXCR2 ligands (14,17,21,37).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that inhibitors of TNF-␣ might be useful in reversing the skeletal wasting seen in COPD as well as reducing the airway inflammatory response (Barnes, 2001a).…”
Section: Effectsmentioning
confidence: 99%
“…These NF-B regulated mediators (e.g., TNF␣, IL-8, IL-6, IL-1␤, MIP-1␣, and GRO␣) have been suggested to play a central role in a variety of acute and chronic inflammatory diseases (Barnes, 2001). Therefore, it has been suggested that blocking the NF-B pathway represents a possible disease-modifying therapy (Barnes and Adcock, 1997).…”
mentioning
confidence: 99%